On generalization of ⊕-cofinitely supplemented modules - Nisanci, B.; Pancar, A. (Український математичний журнал, 2010)
We study the properties of ⊕-cofinitely radical supplemented modules, or, briefly, cgs ⊕-modules. It is shown that a module with summand sum property (SSP) is cgs ⊕ if and only if M/w Loc⊕ M (w Loc⊕ M is the sum of all w-local direct summands of a module M) does not contain any maximal submodule, that every cofinite direct summand of a UC-extending cgs ⊕-module is cgs ⊕, and that, for any ring R, every free R-module is cgs ⊕ if and only if R is semiperfect.